Higher education contributing to local, national, and global development: new empirical and conceptual insights - Chankseliani, Maia; Qoraboyev, Ikboljon; Gimranova, Dilbar (Higher education, 2021)
Higher education offers the potential to support glonacal (global, national, and local) development. This study presents new empirical and conceptual insights into the ways in which higher education can help to achieve and exceed the outcomes enshrined in the Sustainable Development Goals. Open-ended online surveys were used to learn how academics in Georgia and Kazakhstan view the contributions of universities to addressing self-identified development challenges; and how universities work with the government and the private sector for realising their glonacal development potential. While the study provides ample evidence on the national manifestations of the developmental role of universities, it also shows that limited academic freedom and institutional autonomy impede the full realisation of the potential of higher education. The assumptions underpinning the academics’ views on how higher education can support development are discussed in the light of an innovative framework of essentialist and anti-essentialist approaches. Juxtaposing the national with the global development missions of universities, the paper raises questions on the possibility of delinking higher education from the immediate human capital and modernisation needs of the nation-state and becoming concerned with the global, on promoting freedom to cultivate intellectual curiosity through education and research, and stimulating a more holistic imaginary of the developmental purposes of higher education.